Current insights for catheter-directed therapies in acute pulmonary embolism: Systematic review and our single-center experience - Kaymaz, Cihangir; Tokgöz, Hacer Ceren; Kültürsay, Barkın; Hakgör, Aykun; Keskin, Berhan; Sekban, Ahmet; Karagöz, Ali (NLM (Medline), 2023)
In this review, the current status of the worldwide experience on different catheter-directed treatment systems utilized as alternative reperfusion methods in acute pulmonary-embolism was evaluated, and the risk stratification algorithms in which catheter-directed treatments may be implemented, source of evidence in this setting, adjudication of benefits and risks of available techniques, and innovative multidisciplinary frameworks for referral patterns and care delivery were discussed. Moreover, our perspectives on risk-based catheter-directed treatment utilization strategies in acute pulmonary embolism were summarized.
Keywords: Ultrasound-Assisted Thrombolysis; Rheolytic Thrombectomy; Catheterdirected Thrombolysis; Catheter-Directed Thrombectomy; Pulmonary Embolism